2021
DOI: 10.17509/ijal.v10i3.31753
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' beliefs and practices in teaching reading at Islamic secondary schools in Indonesia

Abstract: The importance of English reading skills in developing overall English literacy has made reading instruction one of the primary focuses in Indonesia's English teaching. Regardless of the high value of reading skills, the teaching of reading has not been successful in developing the reading comprehension ability of Indonesian students. This exploratory case study research examines teachers' beliefs and practices in teaching reading in Islamic secondary schools. It focuses mainly on how teachers view good readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…They further acknowledged the significance of the instruction to help their students reading skills. As was also found in a previous study about the importance of teaching pronunciation in Indonesian English classrooms (Moedjito, 2016) and the need to explore new methods in teaching comprehension (Nurkamto et al, 2021), the two participating teachers agreed that there were benefits in the phonics instruction. They raised the possibility of integrating it into the school's English curriculum.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…They further acknowledged the significance of the instruction to help their students reading skills. As was also found in a previous study about the importance of teaching pronunciation in Indonesian English classrooms (Moedjito, 2016) and the need to explore new methods in teaching comprehension (Nurkamto et al, 2021), the two participating teachers agreed that there were benefits in the phonics instruction. They raised the possibility of integrating it into the school's English curriculum.…”
Section: Discussionsupporting
confidence: 66%
“…In the context of EFL learning in Indonesia, teaching reading focuses more on aiming at comprehension skills rather than learning to accurately sound out English words (Cahyono, 2006;Muhassin et al, 2021). More practices were developed aiming for comprehension skills involving vocabulary mastery (Nurkamto et al, 2021) and practical strategies such as a fix-up strategy (Muhassin et al, 2021), the think-aloud method (Pradana, 2017), and frequent techniques of evaluating, organizing, visualizing, and summarizing (Kissau & Hiller, 2013). Still, those research-based practices had not yet been considered, including teaching pronunciation in reading instructions.…”
Section: Efl Teaching Reading In Indonesian Schools and Phonics Instr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the participants in this study found benefits from the implementation of certain teaching practices to develop students' reading comprehension such as types of question-answer relationship strategy, journal reading, making posters and presentations. Thus, teaching reading is consistently considered challenging (Nurkamto et al, 2021).…”
Section: How Do the Teaching Practices Contribute To The Development Of Students' Critical Reading Skills?mentioning
confidence: 99%
“…It is crucial for primary and secondary school-age children. The absence of these skills is an essential problem faced in many Indonesian learning courses and urges undergraduates to study exclusively at primary and secondary schools (Nahdi et al, 2020;Nurkamto et al, 2021;Yuwono et al, 2021). However, the debate continues where many researchers limit screen time for children because it affects their motor, psychological, and cognitive development (REF).…”
Section: Introductionmentioning
confidence: 99%